Hybrid Nanoparticle Pyramids for Intracellular Dual MicroRNAs Biosensing and Bioimaging. Issue 19 (21st February 2017) - Li, Si; Xu, Liguang; Sun, Maozhong; Wu, Xiaoling; Liu, Liqiang; Kuang, Hua; Xu, Chuanlai
Abstract : This study strategically fabricates multifunctional nanopyramids to allow the ultrasensitive quantification of dual microRNAs (miR‐203 b and miR‐21) in living cells and their responsive bioimaging in vivo. The nanopyramids, composed of Au‐Cu9 S5 nanoparticles (NPs), upconversion NPs (UCNPs), and Ag2 S NPs, emit two luminescent signals simultaneously with excitation at 808 nm, arising from the UCNPs at 541 nm in the visible region and from the Ag2 S NPs at 1227 nm in the second window of near‐infrared (NIR‐II) region. The upconversion luminescence has a linear relationship with miR‐203 b from 0.13 to 54.54 fmol per 10 µgRNA and a limit of detection (LOD) of 0.09 fmol per 10 µgRNA, whereas the Ag2 S NP luminescence has a linear relationship with miR‐21 from 0.37 to 43.56 fmol per 10 µgRNA, with a LOD of 0.23 fmol per 10 µgRNA . Significantly, this study demonstrates that the nanopyramids can be successfully used for miRs‐responsive bioimaging in a tumor‐bearing animal model. Furthermore, taking advantage of the photothermal capabilities of pyramids, the tumors can also be eliminated completely. These nanopyramids not only overcome the obstacles in the simultaneous detection of multiple miRs at the cellular level but also provide a cancer theranostic platform in vivo. Abstract : Multifunctional nanopyramids have been fabricated using Au‐Cu9 S5, Ag2 S, and upconversion nanoparticles, which emit reliable up and down conversion luminescence signals simultaneously. They are applied to ultrasensitive detection of dual microRNAs in living cells. Significantly, the miR‐responsive duplexed bioimage sensing has been successfully achieved in a tumor‐bearing animal model at a single excitation.